MEDIATIZATION OF PESANTREN DA'WAH ON TIKTOK LIVE: NEGOTIATING RELIGIOUS AUTHORITY WITHIN DIGITAL PLATFORM LOGIC - Qonita Maulidia; Kun Wazis; Siti Raudhatul Jannah (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
Social media has increasingly repositioned pesantren-based religious instruction from closed, face-to-face gatherings into open, platform-mediated spaces, a shift clearly visible in the TikTok Live broadcasts hosted by Pondok Pesantren Darullughah Wal Karomah (Maktuba DWK) in Kraksaan, Probolinggo. Employing a qualitative case-study design, this research gathered data through non-participant observation, digital documentation, in-depth interviews, and analysis of audience interaction, then analyzed the material using the interactive model of Miles et al. (2014), with trustworthiness confirmed through triangulation. The findings reveal that pesantren preaching is being mediatized, moving away from single-source authority toward participatory, dialogical exchange; that TikTok's recommendation algorithm functions as a gatekeeping mechanism regulating the reach of religious broadcasts; and that religious authority is continually renegotiated among the pesantren, its audience, and the platform. The study proposes a Pesantren Algorithmic Da'wah Ecosystem model, extending mediatization-of-religion theory within the Indonesian pesantren context and offering practical insight for digitally engaged religious institutions.